A numerical investigation of oblique detonation waves in hydrogen-air mixtures at low mach numbers. (11th March 2021) - Teng, Honghui; Bian, Jing; Zhou, Lin; Zhang, Yining
Abstract: Oblique detonation waves (ODWs) have potential applications in hypersonic propulsion, but the boundary of steady ODWs has not yet been examined comprehensively. In this study, Euler equations coupled with detailed chemical reaction models are used to simulate ODWs in hydrogen-air mixtures with relatively low flight Mach numbers (from 7 to 8) and different flight altitudes (30 km and 25 km). Decreases in the flight Mach number and altitude are shown to result in unsteady ODWs in a stoichiometric hydrogen-air mixture. These ODWs can be re-stabilized by decreasing the fuel‒air equivalence ratio. Regardless of different parameters of Mach number and altitude, unsteady ODWs appear only when the velocity in the induction zone exceeds that of the corresponding Chapman-Jouguet detonation. A low equivalence ratio also induces a long initiation length, limiting the availability of decreases in the equivalence ratio to maintain a steady ODW in practical applications. A flow‒combustion criterion is proposed for the application of ODWs, based on the steadiness of ODWs and fast initiation. Graphical abstract: Image 1 Highlights: Oblique detonations near the low flight speed/altitude boundary have been studied. Unsteady waves can be re-stabilized by decreasing the fuel‒air equivalence ratio. A Mach number analysis at the steady boundary clarifies the stabilization mechanism. A flow‒combustion criterion is proposed for the application of shcramjet engines.